SARS-CoV-2 antibody dynamics and B-cell memory response over time in COVID-19 convalescent subjects. (September 2021) - Achiron, Anat; Gurevich, Michael; Falb, Rina; Dreyer-Alster, Sapir; Sonis, Polina; Mandel, Mathilda
Abstract: Objectives: The worldwide spread of coronavirus disease 2019 (COVID-19) highlights the need for assessment of long-term humoral immunity in convalescent subjects. Our objectives were to evaluate long-term IgG antibody response to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and B-cell memory response in COVID-19 convalescent subjects. Methods: Blood samples were collected from a cohort of subjects recovering from COVID-19 and from healthy subjects who donated blood. SARS-CoV-2 IgG antibodies were quantitatively detected by ELISA using anti-S1 spike IgG. SARS-CoV-2 spike-specific IgG memory B cells were evaluated by reversed B-cell FluroSpot based on human IgG SARS-CoV-2 receptor-binding domain in a randomly selected group of subjects recovering from COVID-19. Statistical analysis was performed with clinical variables and time post COVID-19 infection. Results: Antibody response was not detected in 26 of 392 COVID-19 convalescent subjects (6.6%). Over a period of 9 months, the level of antibodies decreased by 50% but stabilized at 6 months, and a protective level prevailed for up to 9 months. No differences were found regarding IgG SARS-CoV-2 antibody levels for age, gender, and major blood types over time. Over time, asymptomatic COVID-19 subjects did not differ in antibody level from subjects with mild to severe disease. Repeated paired IgG SARS-CoV-2 antibody level analyses disclosed that, over 6 and 9 months, 15.3% (nine of 59) and 15.8% (three of 19) of subjects became SARS-CoV-2 IgG-seronegative, respectively, all with a low antibody level at 3 months. Rate of antibody decline was not affected by age, gender, or clinical symptomatology. In a subgroup of recovering subjects, memory B-cell response up to 9 months post-COVID-19 infection was undetectable in 31.8% of subjects (14/44), and there was no correlation with age, SARS-CoV-2 antibody level, or time post infection. Conclusions: The majority of convalescent COVID-19 subjects develop an IgG SARS-CoV-2 antibody response and a protective level prevails over a period of up to 9 months, regardless of age, gender, major blood types or clinical symptomatology.